4-Carboxyanilinium dihydrogen phosphate monohydrate, an organophosphate adducts of 4-amino benzoic acid: Structural, vibrational, thermal, and computational studies - Panicker, Lata (European Journal of Chemistry, 2024)
4-Carboxyanilinium dihydrogen phosphate monohydrate (4-CAH2PO4·H2O), an organophosphate adduct, was synthesized and characterized by single-crystal X-ray diffraction, Fourier transform infrared (FTIR), Differential scanning calorimetry (DSC) and computational analysis performed using CrystalExplorer 21, Gaussian 09W and Multiwfn 3.7 software. The complex 4-CAH2PO4·H2O crystallized in the triclinic space group, P-1, with two molecules each of 4-carboxyanilinium (4-CA) cations, H2PO4– anions, and water, respectively, in an asymmetric unit. Crystal data for C7H12NO7P: triclinic, space group P-1, a = 8.5238(2) Å, b = 8.9068(2) Å, c = 14.4976(4) Å, α = 106.456(2)°, β = 90.195(2)°, γ = 92.811(2)°, V = 1054.13(5) Å3, Z = 4, T = 293 K, μ(Cu Kα) = 2.587 mm-1, Dcalc = 1.595 g/cm3, 18182 reflections measured (6.358° ≤ 2Θ ≤ 146.396°), 4149 unique (Rint = 0.1018, Rsigma = 0.0521) which were used in all calculations. The final R1 was 0.0584 (I > 2σ(I)) and wR2 was 0.1712 (all data). The organic layer containing 4-CA cations and the inorganic layer containing phosphate anions and water molecules in 4-CAH2PO4·H2O crystals are connected through a three-dimensional network of strong charge-assisted N–H···O and C-OH···O hydrogen bonds. The fingerprint plot of 4-CAH2PO4·H2O obtained indicated that the most prominent interaction corresponds to the short O···H contact, followed by the H···H and H···C contacts. The intermolecular interaction topology of 4-CAH2PO4·H2O has been quantitatively analyzed. The 4-CAH2PO4·H2O complex was optimized by density functional theory (DFT) with B3LYP/6-31G basis set and the theoretical IR vibrational spectra determined. The noncovalent interaction (NCI) and quantum theory of the atom in the molecule (QTAIM) analysis were done using Multiwfn 3.7 software. 4-CAH2PO4·H2O complex structure and its computational analysis are also compared with that of 4-carboxyanilinium dihydrogen phosphate (4-CAH2PO4).